Making Money Using Math. - MEIJER, ERIK (Communications of the ACM, 2017)
The article discusses the role mathematics (math) plays in probabilistic computer programming and machine learning (ML), including its role in the development of computer algorithms. An overview of Bayes' rule, including its role in connecting computer programming languages with ML, is provided.